Influence of the electrode nano/microstructure on the electrochemical properties of graphite in aluminum batteries. Issue 45 (31st October 2018) - Greco, Giorgia; Tatchev, Dragomir; Hoell, Armin; Krumrey, Michael; Raoux, Simone; Hahn, Robert; Elia, Giuseppe Antonio
Abstract : Nano-microstructural evolution of PG electrodes in Al-batteries has been investigated by XRD, SAXS and CT evidencing the effect of porosity variation on the cycling behavior. Abstract : Herein we report on a detailed investigation of the irreversible capacity in the first cycle of pyrolytic graphite electrodes in aluminum batteries employing 1-ethyl-3-methylimidazolium chloride:aluminum trichloride (EMIMCl:AlCl3 ) as electrolyte. The reaction mechanism, involving the intercalation of AlCl4 − in graphite, has been fully characterized by correlating the micro/nanostructural modification to the electrochemical performance. To achieve this aim a combination of X-ray diffraction (XRD), small angle X-ray scattering (SAXS) and computed tomography (CT) has been used. The reported results evidence that the irreversibility is caused by a very large decrease in the porosity, which consequently leads to microstructural changes resulting in the trapping of ions in the graphite. A powerful characterization methodology is established, which can also be applied more generally to carbon-based energy-related materials.